Structural Relationship Analysis between Diverse Variables of Employees and Organizational Performance Using Path Analysis - Yong Park, Soo; Kyu Kwon, Hong; Eui Nahm, Yoon; Hyung Lee, Dong; ., . (International Journal of Engineering and Technology, 2018)
The study purpose is to analyze the structural interrelations between life position, activities of learning organization, and job engagement, which can affect organizational performance for corporate survival and prosperity. This study is to analyze the structural relationships between these three variables and organizational performance. To do this, a research model was built on the basis of literature review. And also a survey was conducted in regular employees at 100 companies, collecting 787 data. The collected data were used to test a structural equation model through the AMOS 21.0 and Mplus 7.2 programs. On this study, the following results are achieved; first, activities of learning organization affect organizational performance in companies. Therefore, managers need to make efforts to activate activities of learning organization in pursuit of corporate growth and development. Activities of learning organization also directly affect life position and job engagement. In particular, they had stronger direct effects on job engagement than on life position. Second, job engagement, which is an intrinsic variable, is an important variable affecting organizational performance. Job engagement is not only affected directly by life position, which indirectly affects organizational performance, but also is affected by activities of learning organization, which directly affect organizational performance, and directly affects organizational performance. Third, organizational performance cannot be explained or predicted by one or two specific variables but be effective through complement and interaction among activities of learning organization, life position, job engagement, and so on. The results are applied to suggest the need to develop a strategy for practicing the activities of learning organization and give implications for spreading positive organizational behaviors within an organization.Â